What you bring on yourself - Centron Corporation; Centron Films; Coronet (Firm). (Northbrook, Illinois Coronet MTI Film & Video, 1984)
Defines stress and tells the dangers of unrelieved stress. Describes stress encountered in everyday life and stemming from internal, personal sources, and suggests things that can be done to manage it.
With 1 converted disc.
Distributed by International Book Center.
Keywords: Stress (Psychology); Stress mangement; Job stress